Minimum effective concentration 90 (EC90) of ropivacaine for Femoral nerve block: A biased-coin up-and-down sequential method study - Ahmed M. Taha; Manjusha Mohanan; Sebastian Orduna; Ahmed F. Alalwi; Mohamed I. Badr; Ahmed M. Abd-Elmaksoud (Indian Journal of Anaesthesia)
Background and Aims: The femoral nerve (FN) is commonly blocked using ropivacaine to provide postoperative analgesia after knee surgery. However, the minimal required concentration has not yet been defined. The aim of this study was to estimate the minimal ropivacaine concentration required to achieve adequate analgesic FN block in 90% of cases (EC90). Methods: This study included 50 patients who were scheduled for knee ligament reconstruction under combined nerve block and general anaesthesia. The FN block was performed using 15 mL of ropivacaine with varying concentrations and considered adequate when associated with pain-free recovery. The sciatic, obturator, and lateral femoral cutaneous nerves were blocked to negate other knee pain generators, and their block success was confirmed. We used the biased-coin design up–down sequential method where the adequacy of an FN block altered the ropivacaine concentration used for the next block. The adequacy of the analgesic block or lack of it was analysed to calculate the analgesic EC90. The quadriceps motor power and morphine requirement were also recorded. Results: The recommended analgesic ropivacaine EC90 was 0.05% w/v. The associated quadriceps weakness and morphine requirement were minimal. Conclusion: FN block using ropivacaine 0.05% w/v may provide adequate analgesia in 90% of patients.